Pemberdayaan Lahan Sempit Bagi Masyarakat Perkotaan dalam Meningkatkan Minat Berwirausaha pada Subsektor Usaha Tani Perkotaan - Kamaruddin, Citra Ayni (Department of Economics Education, Faculty of Economics, Universitas Negeri Makassar, 2023)
Land management is the process of making and planning decisions, directing, organizing, and managing human, physical, financial, and information resources to achieve organizational goals in efficient and effective land management. Changes in land use in urban areas are increasing along with urban expansion and development. Trends in land use in metropolitan areas reflect economic and demographic expansion, as well as societal preferences as drivers of land use change. To achieve household food self-sufficiency and sustainable urban growth, urban areas need regulations to limit changes in land use. Agricultural techniques in urban environments are currently developing according to zone features and land availability. Vegetables, horticultural, ornamental, and medicinal plants are the only crops grown in the city. The purpose of this research is to show how limited urban space can be used for agriculture and family food self-sufficiency.